Betrayal in death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2001)
At the luxurious Roarke Palace Hotel, a maid walks into suite 4602 for the nightly turndown - and steps into her worst nightmare. A killer leaves her dead, strangled by a thin silver wire. He's Sly Yost, a virtuoso of music and murder. A hit man for the elite. Lieutenant Eve Dallas knows him well. But in this twisted case, knowing the killer doesn't help solve the crime. Because there's someone else involved. Someone with a more personal motive. And Eve must face a terrifying possibility - that the real target may, in fact, be her husband Roarke.